2015
DOI: 10.4103/0377-4929.168875
|View full text |Cite
|
Sign up to set email alerts
|

Association of virulence genes with mecA gene in Staphylococcus aureus isolates from Tertiary Hospitals in Nigeria

Abstract: The study concluded that there is a high prevalence of MRSA in Nigeria with association of eta and icaA genes with mecA gene in S. aureus isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
5
17
3
Order By: Relevance
“…Regarding other reports, the complex role of mecRI in the pathogenicity of MRSA strains can be concluded. They also confirmed that the cooperation of VFs and regulating β-lactamase genes also play a critical role in increasing the pathogenicity of S. aureus isolates [ 15 , 29 31 ].…”
Section: Discussionmentioning
confidence: 72%
“…Regarding other reports, the complex role of mecRI in the pathogenicity of MRSA strains can be concluded. They also confirmed that the cooperation of VFs and regulating β-lactamase genes also play a critical role in increasing the pathogenicity of S. aureus isolates [ 15 , 29 31 ].…”
Section: Discussionmentioning
confidence: 72%
“…Slime production is considered as a significant virulence factor for some strains of staphylococci [16]. The pathogenicity of S. aureus depends on various virulence factors associated with adherence, evasion of the immune system and damage of the host [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Virulence factors of S. aureusinclude slime formation, secreted enzymes, toxins like lipases, DNase, proteases, hemolysins and some super antigens like toxic shock syndrome toxin and enterotoxin [5]. The pathogenicity of S. aureus depends on various virulence factors associated with adherence, evasion of the immune system and damage of the host [6,7]. The presence of…”
Section: Introductionmentioning
confidence: 99%
“…In surgical site infections for 103 patients with orthopedic surgery in a hospital in Port Harcourt, Nigeria, the commonest pathogen was S. aureus (34%) including 15 patients with MRSA [27]. and prevalence of MRSA with mecA gene as 42.3% from 156 S. aureus in clinical isolates from South Western Nigeria with domination of SCCmec II and SCCmec V [28].…”
Section: Mrsa Prevalence In Africamentioning
confidence: 99%